Protein Ligand Docking Study of Cetirizine on HERG Receptor - Shukla, Kavita Varma; Sharma, Vishal (International Journal of Computer Sciences and Engineering, 2025)
HERG is the protein which is found in the potassium ion channel which is mainly used to check the cardiac action of heart in which we can see the heart rhythm and its abnormality by the Q.T syndrome through electro gram where Q.T interval was extended or prolonged for that the various reports are coming for sudden death due to cardiac arrest.